Analysis of the effect of two-wheeler lane-sharing behavior on macroscopic traffic flow modeling - Chunchu, Mallikarjuna; Kuzhiyamkunnath, Bhavathrathan B. (Transport, 2014)
Small size motorized vehicles such as the motorized two-wheelers are predominantly present in the traffic observed in the developing countries. Presence of these smaller vehicles invalidates the concept of lane discipline commonly observed in the homogeneous traffic streams. In this paper an attempt has been made to understand the Motorized Two-Wheeler (MTW) lane-sharing behavior and its effects on traffic flow modeling. The objectives of this attempt are to analyze the lane-sharing behavior of MTWs at microscopic and macroscopic level, and to propose a methodology to incorporate this behavior in the macroscopic modeling concepts. Effect of the MTW lane-sharing behavior on the microscopic and macroscopic traffic characteristics and the corresponding models is discussed. A plausible way to incorporate this behavior, specifically in macroscopic modeling, is discussed. From a specific analysis based on VISSIM (version 5.20) it has been observed that the MTW lane-sharing behavior significantly influence the equilibrium speed-density relationships which are the key inputs to the macroscopic traffic flow models. Density diminishing factor is found to be significantly influenced by the proportion of MTWs present in the traffic stream. It has been observed that the lane-sharing behavior starts taking place when the average stream speed is less than 65 km/hr, for the proportions of MTWs in between 25 to 60%. For further higher MTW proportions lane-sharing has been observed even in free flow conditions.